-4x-1-3x-4+5 = -7x-1-2x+1+6 -7x = -9x+6 2x = 6 x = 3
-(3x-4) = -3x + 4
12x - 4 = 7x - 21 12x -7x = -21 + 4 5x = -17 x = -3.4
The expression simplifies to: -7x-4
The sum of the coefficients is 3 - 7 + 4 = 0 so (x - 1) is a factor. Thus, 3x2 - 7x + 4 = 3x2 - 3x - 4x + 4 = 3x(x - 1) - 4(x - 1) = (3x - 4)(x - 1)
3/x-5 - 4/5-x 3(5-x) -4(x-5) 15-3x-4x+20 35-7x
k = 7 x^4 - 5x^3 + 7x^2 + 3x - 10 = (x + 1)(x - 2)(x^2 - 4x + 5)
3x-8=7x+10x 3x-8=17x -8 = 14x -4=7x -4/7
It is: x-1+4+7x-3 = 8x simplified
(x+4)(x-7)
3x2 -14x -24 can be factored as (3x + 4)(x - 6).
3x2 - 11x - 4 = (x-4)(3 x + 1)